Skip to content
Related Articles

Related Articles

Improve Article

Solve the Equation x = 4/5(x + 10)

  • Last Updated : 21 Jul, 2021

Linear equations in one variable are equations that are written as ax + b = 0, where a and b are two integers and x is a variable, and there is only one solution. 3x+2=5, for example, is a linear equation with only one variable. As a result, there is only one solution to this equation, which is x = 3/11. A linear equation in two variables, on the other hand, has two solutions.

A one-variable linear equation is one with a maximum of one variable of order one. The formula is ax + b = 0, using x as the variable.

There is just one solution to this equation. Here are a few examples:

  • 4x = 8
  • 5x + 10 = -20
  • 1 + 6x = 11

Linear equations in one variable are written in standard form as:

ax + b = 0 



Here, 

  • The numbers ‘a’ and ‘b’ are real.
  • Neither ‘a’ nor ‘b’ are equal to zero.

Solving Linear Equations in One Variable

The steps for solving an equation with only one variable are as follows:

Step 1: If there are any fractions, use LCM to remove them.

Step 2: Both sides of the equation should be simplified.

Step 3: Remove the variable from the equation.

Step 4: Make sure your response is correct.

For Example:



Consider the equation: 4x – 3 = -2x + 12

Solving the above equation for x as follows:

4x – 3 = -2x + 12

4x + (-2x) = 12 + 3

2x = 15

x = 15/2

Solve the Equation x = 4/5(x + 10)

Solution:

Given that,

x = 4/5 (x +10)

When we multiply both sides by 5, we get

5x = 4 (x + 10)

5x = 4x + 40

After subtracting 4x from both sides, we obtain that

5x – 4x = 4x + 40 – 4x

x = 40

Hence, the value of x is 40.

Similar Questions

Question 1: Solve for z, 2z = 4z +2.

Answer:

Given that,

2z = 4z + 2

After subtracting 4z from both sides, we obtain that

2z – 4z = 4z + 2 – 4z

-2z = 2

Let’s divide both side of the above equation by -2 as,

x = -1

Question 2: Solve for y, 2y – 4 = 0

Answer:

Given that,

2y – 4 = 0

After subtracting 2y from both sides, we obtain that



2y – 2y – 4 = 0 – 2y

-4 = -2y

or 

4 = 2y

Let’s divide both side of the above equation by 2 as,

y = 2

Attention reader! Don’t stop learning now. Join the First-Step-to-DSA Course for Class 9 to 12 students , specifically designed to introduce data structures and algorithms to the class 9 to 12 students

My Personal Notes arrow_drop_up
Recommended Articles
Page :